A biscuit fortified with iron, iodine and B-carotene as a strategy to address micronutrient deficiencies in primary school children - Van Stuijvenberg, Martha Elizabeth (Not Specified, 2023)
Deficiencies of vitamin A, iron, and iodine continue to be prevalent in developing countries worldwide and can, in addition to the classic consequences such as nutritional anaemia, goitre, cretinism, xerophthalmia and blindness caused by severe deficiencies, also affect the growth, development and immunity of young children. The various internationally acknowledged strategies for combating micronutrient deficiencies include high-dose supplementation, food fortification, dietary diversification and nutrition education. The aim of this research was to evaluate a micronutrient-fortified biscuit as a strategy to address micronutrient deficiencies in primary school children from a poor rural community. The research comprised three phases. During the first phase the effect of a biscuit fortified with iron, iodine, and B-carotene on the vitamin A, iron and iodine status of 115 children was evaluated and compared with 113 controls, in a randomised placebo-controlled trial. To enhance the absorption of iron a vitamin C-fortified cold drink was given together with the biscuit. Anthropometric status, cognitive function and morbidity were assessed as secondary outcomes. The 12-month intervention resulted in a significant improvement in serum retinol, serum ferritin, transferrin saturation, haemoglobin and urinary iodine excretion. Morbidity and cognitive function, particularly the cognitive function in the children presenting with low iron status and with goitre! at baseline, were also favourably affected. Linear growth was positively affected only in the children with marginal iron stores at baseline. During the second phase of this study the long-term effectiveness of the biscuit programme, in terms of elimination of micronutrient deficiencies, compliance, acceptability and sustainability, was evaluated in a longitudinal study over a period of 30 months. In addition, cross-sectional data on vitamin A and iron status from subsequent studies conducted in the same school at 33, 42 and 45 months after the start of the original biscuit intervention, during which time the fortified biscuit continued to be distributed at the school, are reported. Although micronutrient status improved significantly during the 12 months of the first study, all variables (except urinary iodine) returned to pre-intervention levels when the schools reopened after the summer holiday. Serum retinol increased again during the next nine months, but was significantly lower in a subsequent survey, carried out directly after the summer holiday; this pattern was repeated in two further cross-sectional surveys. Iron status showed no recovery during a subsequent intervention period when the vitamin C-fortified cold drink was supplied on a less frequent basis, or during the period that ferrous bisglycinate was used as iron fortificant. Because of the compulsory iodisation of salt, that came into effect halfway through the first phase of the study, improved iodine status, as measured by urinary iodine excretion, was maintained. In the third phase of the research, red palm oil, a rich natural source of B-carotene, was examined as an alternative vitamin A fortificant in the biscuit. This study contained elements of both a randomised placebo-controlled trial and an equivalence trial. The biscuit with a red palm oil-based shortening was shown to be as effective as the biscuit with fl-carotene from a synthetic source in improving the vitamin A status of these children. In conclusion, the results of the studies described in this thesis showed that a micronutient-fortified biscuit is a feasible, practical and effective way of improving the micronutrient status of primary school children from a poor rural community. Long-term evaluation of this programme, however, showed that improved micronutrient status is not sustained during the long summer school holidays, and it is suggested that the biscuit programme is supplemented with other strategies, such as local food production programmes and nutrition education. Red palm oil, with all of its additional qualities (i.e. no trans fatty acids; rich source of antioxidants), appears to be an attractive alternative for use as a vitamin A fortificant. The choice of the iron compound to be used in the biscuit, however, needs further investigation.